Development of e-learning by Microsoft: from local solutions to cloud services - А. V. Lytvyn (Academy of Cognitive and Natural Sciences, 2015)
The purpose of the study is to analyze the development of Microsoft's e-learning services. The object of the research is the process of using Microsoft's e-learning services. The subject of the study is the Microsoft's e-learning services. The objectives of the study are to analyze the development of Microsoft's e-Learning services (from local cloud solutions to solutions) from the Microsoft Class Server learning platform, then to the Microsoft SharePoint Learning Kit, then to Live@edu and to the online Office service 365. The possibilities for the educational process, advantages and disadvantages of each software product are determined.